Adjusting capitation using chronic disease risk factors: A preliminary study - Howland, Jonathan (CENTERS for MEDICARE & MEDICAID SERVICES, 1987)
Researchers have sought ways to modify Medicare's capitation formula, the adjusted average per capita cost (AAPCC), by including measures of individual health status. The present study assesses the value of risk factors for disease as predictors of hospitalization for Framingham Heart Study participants (1,210 males and 1,496 females) 60-65 years of age. Regression models including several common physiologic measures and prior hospitalizations yielded adjusted R(2)s of 9.69 percent for males and 3.61 percent for females. The contributions of the risk factors and prior hospitalization were about equal and independent. These results confirm the potential utility of disease risk factors for adjusting the AAPCC.